Origin-Destination Matrix as a Way to Create a Basic Algorithm for Simulation a Load of Transport Network - Yablonovskaya, Marina; Shevtsova, Anastasiya; Borovskoy, Alexey (Applied Mechanics and Materials, 2015)
Article is devoted to studying of traffic flows using the origin-destination matrix. The first paragraph of this article deals with the possibility of applying the origin-destination matrix when modeling load of transport network. The types of transportations, the factors that affect the loading of the transport network are described. The concept of a generalized path cost, interdistrict transportations and some others are considered. There are proposed several steps to create a origin-destination matrix. In the second paragraph of the paper is proposed the classification of mathematical models that can be applied in the simulation of traffic flow, as well as their features are marked. This will help in the processing of data for selection of a mathematical model that satisfies the requirements and objectives that have set themselves researchers. The conclusions on the application of mathematical models in the study of traffic flow are made.